Thiamine and Pyridoxine Loaded Vanillic Acid Grafted Chitosan Modulates Lactate and Malate Dehydrogenase in Albino Rats - Tejpal, C S; Chatterjee, N S; Elavarasan, K; Lekshmi, R.G K; Anandan, R; Asha, K K; Ganesan, B; Mathew, Suseela (Fishery Technology, 2017)
Feeding trials was conducted to study the responseof metabolic enzymes activity such as lactatedehydrogenase (LDH) and malate dehydrogenase(MDH) through dietary supplementation of thiamineand pyridoxine loaded vanillic acid graftedchitosan microparticles (TPVGC) in male and femaleWistar strain albino rats for a period of 45 days.Forty-eight animals both male and female wererandomly distributed into eight experimental groupsand were fed with basal feed along with differentlevels of TPVGC. At the end of the experiment, theLDH activity in both male and female Wistar strainalbino rats were found to be significantly higher(p